Ambient Chemical Fixation of CO2 Using a Robust Ag27 Cluster‐Based Two‐Dimensional Metal–Organic Framework. Issue 45 (31st August 2020) - Zhao, Meihua; Huang, Shan; Fu, Qiang; Li, Weifeng; Guo, Rui; Yao, Qingxia; Wang, Fenglong; Cui, Ping; Tung, Chen‐Ho; Sun, Di
Abstract: Unprecedented double S 2− templated Ag27 clusters have been stabilized by 5, 10, 15, 20‐tetra(4‐pyridyl)porphyrin (TPyP‐H2 ) ligands to afford a robust 2D metal–organic framework (Ag27‐MOF ). This silver cluster‐assembled material serves as a highly efficient heterogeneous catalyst for the cyclization of both terminal and internal propargylamines with CO2 under atmospheric pressure. Density functional theory (DFT) calculations illustrate that the high catalytic activity and broad substrate scope are attributable to the saddle‐shaped metallic node in Ag27‐MOF, which features an accessible platform with high‐density silver atoms as π‐Lewis acid sites for activating C≡C triple bonds. As a result, different sterically hindered alkyne substrates can be effectively activated through π‐interactions with these cationic silver centers. Abstract : An Ag27 cluster‐assembled 2D MOF has been constructed and employed as the catalyst for carboxylative cyclization of propargylamines with CO2 . Both the high TON number and broad substrate scope confirm Ag27‐MOF to be an excellent heterogeneous catalyst, making a breakthrough in the use of 2D MOFs as high‐performance catalysts.